Dedicated real‐time monitoring system for health care using ZigBee. Issue 4 (7th July 2017) - Alwan, Omar S.; Prahald Rao, K.
Abstract : Real‐time monitoring systems (RTMSs) have drawn considerable attentions in the last decade. Several commercial versions of RTMS for patient monitoring are available which are used by health care professionals. Though they are working satisfactorily on various communication protocols, their range, power consumption, data rate and cost are really bothered. In this study, the authors present an efficient embedded system based wireless health care monitoring system using ZigBee. Their system has a capability to transmit the data between two embedded systems through two transceivers over a long range. In this, wireless transmission has been applied through two categories. The first part which contains Arduino with ZigBee will send the signals to the second device, which contains Raspberry with ZigBee. The second device will measure the patient data and send it to the first device through ZigBee transceiver. The designed system is demonstrated on volunteers to measure the body temperature which is clinically important to monitor and diagnose for fever in the patients.